To simplify the expression we are going to use the distributive property of multiplication:
![a(b+c)=ab+ac](https://tex.z-dn.net/?f=a%28b%2Bc%29%3Dab%2Bac)
.
We can infer from our problem that
![a=-2x^2](https://tex.z-dn.net/?f=a%3D-2x%5E2)
,
![b=4x](https://tex.z-dn.net/?f=b%3D4x)
, and
![c=-3](https://tex.z-dn.net/?f=c%3D-3)
. So lets apply the property to simplify our expression:
![-2x^2(4x-3)=(-2x^2)(4x)+(-2x^2)(-3)](https://tex.z-dn.net/?f=-2x%5E2%284x-3%29%3D%28-2x%5E2%29%284x%29%2B%28-2x%5E2%29%28-3%29)
We can conclude that the correct answer is <span>
-8x3 + 6x2</span>
Answer:
The independent variable is x and the dependent variable is y.
Answer:It's A becauseits the only answer that says less than, the others say more than and less than or equal to.
Step-by-step explanation: